2015
DOI: 10.1080/15548627.2015.1094597
|View full text |Cite
|
Sign up to set email alerts
|

Elevated autophagy gene expression in adipose tissue of obese humans: A potential non-cell-cycle-dependent function of E2F1

Abstract: Autophagy genes' expression is upregulated in visceral fat in human obesity, associating with obesity-related cardio-metabolic risk. E2F1 (E2F transcription factor 1) was shown in cancer cells to transcriptionally regulate autophagy. We hypothesize that E2F1 regulates adipocyte autophagy in obesity, associating with endocrine/metabolic dysfunction, thereby, representing non-cell-cycle function of this transcription factor. E2F1 protein (N=69) and mRNA (N=437) were elevated in visceral fat of obese humans, corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 89 publications
(108 citation statements)
references
References 78 publications
2
106
0
Order By: Relevance
“…602,608 In the clinical setting, tissue expression of ATG5, LC3A and LC3B and their respective proteins accompanies elevated autophagy flux in human adipose tissue in obesity. 217,609 Thus, assessing the mRNA levels of LC3 and other autophagy-related genes by northern blot or qRT-PCR may provide correlative data relating to the induction of autophagy. Downregulation of autophagy-related mRNAs has been observed in human islets under conditions of lipotoxicity 409 that impair autophagic flux.…”
Section: Transcriptional Translational and Posttranslational Regulationmentioning
confidence: 99%
“…602,608 In the clinical setting, tissue expression of ATG5, LC3A and LC3B and their respective proteins accompanies elevated autophagy flux in human adipose tissue in obesity. 217,609 Thus, assessing the mRNA levels of LC3 and other autophagy-related genes by northern blot or qRT-PCR may provide correlative data relating to the induction of autophagy. Downregulation of autophagy-related mRNAs has been observed in human islets under conditions of lipotoxicity 409 that impair autophagic flux.…”
Section: Transcriptional Translational and Posttranslational Regulationmentioning
confidence: 99%
“…Regulation of autophagy has been studied in the context of aging, cellular development and cellular defense against pathogens, and is implicated in the pathogenesis of a growing number of human diseases [15]. In independent study settings and cohorts, we found generally higher markers of autophagy in visceral compared with SC adipose tissue and significant correlations with obesity, insulin resistance and adipose tissue inflammation [49,50,81]. However, since these associations have not been consistently found across different cohorts the dynamic changes due to autophagic flux need to be considered in the discussion of whether autophagy protects against obesity associated adipocyte dysfunction or could contribute to adipose tissue inflammation [82].…”
Section: Autophagy Apoptosis and Immune Cell Infiltration In Adiposementioning
confidence: 75%
“…Individuals with hypertrophic obesity displayed lower improvement of insulin resistance after bariatric surgery [48]. Larger adipocytes are also more prone to store lipophilic toxins, which may increase intracellular stress, autophagy and apoptosis [49,50]. Adipocyte hypertrophy most likely results from a low capacity of de novo adipogenesis and an inability to respond to the energy surplus by adequately increasing adipocyte number (hyperplasia) [51].…”
Section: Initial Mechanisms For the Activation Of Adipose Tissue Inflmentioning
confidence: 99%
“…Under these conditions, TNFα-induced increase in Ask1 mRNA was significantly inhibited by ∼50% (Figure 3D). We previously demonstrated that despite the role of E2F1 in adipogenesis [35], under in-vitro conditions, MEFs from E2F1 −/− mice can differentiate into adipocyte-like cells comparably to MEFs from wild-type (WT) mice, as assessed morphologically and by the similar induction of adipocyte-specific genes (Ppar γ , Cebp4α , Fabp4 , and Glut4 ) [30]. Utilizing these cells, we observed that in the absence of E2F1, “basal” ASK1 expression was markedly attenuated (Figure 3E–G).…”
Section: Resultsmentioning
confidence: 99%